An Exploratory Study of Neoadjuvant Cetuximab Followed by Cetuximab and Chemoradiotherapy in Women With Newly Diagnosed Locally Advanced Cervical Cancer. (7th July 2022) - Fracasso, Paula M.; Duska, Linda R.; Thaker, Premal H.; Gao, Feng; Zoberi, Imran; Dehdashti, Farrokh; Siegel, Barry A.; Uliel, Livnat; Menias, Christine O.; Rehm, Patrice K.; Goodner, Sherry A.; Creekmore, Allison N.; et al.
Abstract : Objectives: This study explored the feasibility of cetuximab with chemoradiation in women with cervical carcinoma and evaluated fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography ( 18 F-FDG-PET/CT) to assess early response to cetuximab (NCT00292955). Patients and Methods: Eligible patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB-IVB invasive carcinoma of the uterine cervix were treated on 1 of 3 dose levels (DL). DL1 consisted of neoadjuvant cetuximab, then concurrent radiotherapy with cetuximab 250 mg/m 2 /cisplatin 40 mg/m 2, followed by weekly cetuximab. DL2 consisted of radiotherapy with cetuximab 200 mg/m 2 and cisplatin 30 mg/m 2 . DL3 consisted of radiotherapy with cetuximab 250 mg/m 2 and cisplatin 30 mg/m 2 . Patients underwent 18 F-FDG-PET/CT before treatment, after neoadjuvant cetuximab, and at the end of treatment. Results: Of the 21 patients enrolled, 9, 3, and 9 were treated in DL1, DL2, and DL3, respectively. DL1 required dose reductions due to gastrointestinal toxicities. DL2 and 3 were tolerated with 1 dose-limiting toxicity (grade 4 renal failure) at DL3. Following 3 weekly treatments of neoadjuvant cetuximab in DL1, 7 patients had maximum standardized uptake value changes on 18 F-FDG-PET/CT consistent with response to cetuximab. Of the 12 patients with locally advanced disease, eleven evaluable patients had no evidence of disease on 18 F-FDG-PET/CT at treatment end. Five-year progression-free survival and overall survival rates for all patients were 57.5% and 58.5%, respectively. Conclusions: Cetuximab with cisplatin 30 mg/m 2 and radiotherapy was tolerated. 18 F-FDG-PET/CT demonstrated early evidence of response to neoadjuvant cetuximab. With advances in precision oncology and the recent approval of pembrolizumab in metastatic cervical cancer, dual-target inhibition with an epidermal growth factor receptor inhibitor may be a promising treatment in the future.